2006
DOI: 10.1080/02770900600925221
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in the Interpretation of Lung Function Tests in the Diagnosis of Asthma and Chronic Obstructive Pulmonary Disease

Abstract: This study raises concerns about differences in the interpretation of spirometry and peak expiratory flow rates in general and hospital practice and the guidelines on which these interpretations are based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…A study by Raghunath et al [33] indicated that there are significant differences in the interpretation of spirometry data between GPs and specialists. Marklund et al [34] examined adults with a diagnosis of asthma from 2 general practices, where in only 60% of patients was this diagnosis confirmed by specialist examination.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Raghunath et al [33] indicated that there are significant differences in the interpretation of spirometry data between GPs and specialists. Marklund et al [34] examined adults with a diagnosis of asthma from 2 general practices, where in only 60% of patients was this diagnosis confirmed by specialist examination.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study concur with the results of EATON et al [5] and show that, generally, GPs have made progress in the interpretation of test results relevant for respiratory diseases in primary care. The current acuity of GPs' interpretation of test results should weaken earlier reported lack of confidence in the ability to interpret the test results [8,9].…”
Section: Spirometry Expert Support and Gps Pjp Poels Et Almentioning
confidence: 99%
“…In 1999, EATON et al [5] had already found that 53% of GPs' interpretation of spirometry test results was judged to be correct according to an expert panel. Recently, RAGHUNATH et al [9] found that the agreement in interpretation of spirometry and peak flow results between nurses, GPs and an expert panel was only 20%. The lower agreement in the latter study could probably be explained by the fact that GPs, as well as nurses, i.e.…”
Section: Spirometry Expert Support and Gps Pjp Poels Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…2) What is the effect of spirometry on a primary-care physician's certainty about a diagnosis, and what are the consequences in terms of ordering of additional diagnostic tests and referrals to specialists? 3) How can we support primary-care physicians with their interpretation of spirometry tests, which is often not as adequate as secondary-care respiratory specialists would like to see [7,8]? Only with well-designed studies that address these questions can we really move the research on the value of spirometry for primary-care physicians and their patients forward.…”
mentioning
confidence: 99%